Concept of Skin Wrinkles (Valitva) in Ayurveda with Special Reference to Tvak Śarīra - Tamhankar, Ketan; Saoji, Sayali; Tayanath, Nutan Narayan; Singh, Tejendra (Journal of Neonatal Surgery, 2025)
Skin aging is a universal biological phenomenon involving progressive structural and functional changes, notably wrinkles, dryness, and a loss of elasticity. In the Ayurvedic tradition, these wrinkles are identified as Valitva or Vālikā, primarily attributed to the predominance of Vāta doṣa and the gradual depletion of bodily tissues (dhātu kṣaya)1. Ayurveda distinguishes between Jarā-janya Valitva (natural physiological wrinkles) and Ayathā-kāla Valitva (premature pathological wrinkles) resulting from improper lifestyle, diet, and stress2. This paper explores the multilayered structure of the skin (Tvak Śarīra) and the Ayurvedic framework for understanding and managing wrinkles3